Maintaining team performance - Kanaga, Kim (Ideas into action guidebooks., 2003)
"Between the time a team is launched and the time it delivers results, managers need to know that the team is on course. Whether they have launched a team to achieve a business objective or have inherited a team, they need to monitor effectiveness on an ongoing basis and make course corrections that keep small problems from becoming major disasters. Monitoring and maintaining team performance is a key element of leading a team. You can provide that leadership by paying attention to four important dimensions: team member effort, team member knowledge and skills, team tactics, and group dynamics. By focusing on those four areas, you can assess your team's performance, zero in on areas of weakness, and take the corrective measures necessary to ensure peak performance and to deliver expected results."--Publisher's description